Pengembangan Dan Implementasi Kebijakan Dalam Peningkatan Mutu Pendidikan Di Perguruan Tinggi - Widiayati; Tati Kusmiati; Eli Sutrisnaniati; Junainah; Mahesa Nur Iman Rudinah; Haeruddin (CV. Multi Kreasi Media, 2022)
Education plays a crucial role in shaping the quality of human resources in a nation. As one of Indonesia’s leading higher education institutions, Universitas Ahmad Dahlan Yogyakarta (UAD) is committed to continuously improving the quality of education, particularly within the Master's Program in Educational Management (PSMMP). The PPL Internship Activity Report provides an overview of the development and implementation of policies to enhance educational quality in the Master’s Program in Educational Management at Universitas Ahmad Dahlan, Yogyakarta. The PPL activities were designed from preparation through execution, evaluation, and reporting stages. Data collection methods included interviews, observations, and documentation. The collected data were analyzed interactively through data reduction, data presentation, and conclusion drawing. From the PPL Internship activities, it was observed that in developing and implementing policies, PSMMP UAD employs several strategies, including: a) conducting an interactive, holistic, integrative, scientific, contextual, thematic, effective, collaborative, and student-centered system of learning, based on research and best practices, b) developing and implementing an outcome-based education curriculum that is student-centered, c) fostering students’ professional, innovative, and dedicated character grounded in progressive Islamic values, d) engaging in community service relevant to the field of educational management, aimed at improving educational practice, and f) publishing scholarly works in educational management in both national and international journals.